Risk Factors of Non-Typhoidal Salmonella Bacteremia Versus Typhoidal Salmonella Bacteremia in Patients from a General Hospital in Karawaci, Tangerang, Indonesia: A Five-Year Review - Lugito, Nata; Cucunawangsih, Cucunawangsih; Kurniawan, Andree; Purnamasari, Dewi (Medicinus, 2019)
Salmonella infections including Non-typhoidal Salmonella (NTS) and enteric fever are important global public health problem, causing approximately 94 million human cases of gastroenteritis with 150,000 deaths annually around the globe. The aim of this study was to determine risk factors for NTS bacteremia patients compared to Typhoidal patients in Indonesia, area with high incidence of enteric fever. This retrospective descriptive study was conducted in Siloam Hospital in Karawaci, Indonesia, from January 2011 to December 2015. Logistic regression model was used to determine independent predictors of NTS bacteremia including demographic and epidemiologic characteristics, clinical presentations, and laboratory results. Out of 129 positive isolates for Salmonella with complete medical records, 18 (13.9%) were positive for NTS. Patients with NTS bacteremia were more likely to belong in the age group below 5 or above 60 year-old, more frequent to have anemia and abnormal leucocyte count. The susceptibility patterns against antimicrobial of NTS bacteremia and Typhoidal bacteremia were similar. In logistic regression analysis, age below 5 or above 60 year-old, hemoglobin level below 12 g/dL and leucocyte count below 4,000/µL or above 12,000/µL were independent risk factors for NTS bacteremia.